EFEKTIVITAS PROGRAM RASTRA DAN PROGRAM BPNT TERHADAP TINGKAT PENDAPATAN DAN KESEJAHTERAAN KELUARGA PENERIMA MANFAAT DI KELURAHAN YUKUM JAYA KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Muthi, Diah Tera Dwi; Ismono, Raden Hanung; Indriani, Yaktiworo (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aimed to determine the implementation, analyze the effectiveness of the implementation, the welfare and income of beneficiaries, the relationship between effectiveness of Rastra and BPNT in addition to the level of income and welfare of beneficiary families in Yukum Jaya Village. The research was conducted by survey method, include location was determined purposively of Yukum Jaya Village. The data was analized qualitative, effectiveness analysis methods, household income, welfare according to the BKKBN and Rank Spearman test. The results showed that the distribution of Rastra and BPNT has not fully complied with the regulations set by Ministry of Social Affairs. The effectiveness of Rastra and BPNT was not effective. The highest average income of Rastra was earned by 7 entrepreneurs in which average income month was Rp5,842,105 and the lowest income was earned by a laundry worker and clothes iron Rp378,947. The highest income of BPNT was earned by 10 vegetables trader with an average income/month of Rp6,659,032 and the lowest income was a tofu trader with an average income/month of Rp587,097. The welfare level of the respondents Rastra was in the stage of prosperous family II (KS II) and prosperous family III (KS III) of BPNT was classified on prosperous family stage III (KS III). There was no positive relationship between the effectiveness of Rastra and BPNT program and the level of income and welfare of beneficiary families. Key words: BPNT, effectiveness, income, Rastra, welfare